Correlation between A, B, and O Blood Group System and Dental Anxiety in Children of Age 6-12 Years in East Bengaluru - Swathi Kakathkar; Ila Srinivasan; Jyothsna V Setty; P Akhil; Clarissa Suting; K M Nayana (Wolters Kluwer Medknow Publications, 2020)
Background: Dental anxiety is a term used to describe fear or stress in a dental setting which a pedodontist has to face routinely. Studies have shown that genetics of blood group plays an important role in human behavior. The genes which code for ABO blood group system are also responsible for the activity of certain neurotransmitters like dopamine. The aim of this study was to assess the correlation between dental anxiety and different blood groups in children. Materials and Methods: The study included 80 healthy children of age 6-12 years requiring Class I and Class II cavity restorations. Dental anxiety was measured using the Animated Emoji Scale during the procedure. Data regarding the blood group of patients were collected using past medical records from parents or guardians. Results: The results showed that the mean dental anxiety score was highest in blood Group AB (3.60), followed by B (2.48), O (2.19), and A (2.00) which was statistically significant. No statistically significant results were found in terms of gender and Rh factor. Conclusion: Dental anxiety scores show a correlation with blood groups.